Mesodiphthera Tillyard, 1919, from the Late Triassic of Queensland, the oldest cicada (Hemiptera: Cicadomorpha: Cicadoidea: Tettigarctidae) - Lambkin, Kevin J. (Zootaxa, 2019)
New specimens of its type species from the Queensland Late Triassic (Norian) (~227–~208.5 Ma) fossil insect locality at Dinmore have revealed that the old and obscure Late Triassic genus Mesodiphthera Tillyard, 1919, from nearby Denmark Hill, is a tettigarctid cicada, the earliest record of the family and the oldest cicada. The genus is distinguished by the combined presence of three characters: the primary forks of R and M at about the same level, midway between the basal cell and the nodal line; RA2 with four or five terminal branches; and the inter-medial cross-vein backwardly inclined, running between M2 and M3. Of the three species originally ascribed to Mesodiphthera by Tillyard, only its type, M. grandis Tillyard, 1919, is retained in the genus. The other two species differ significantly from the type and are transferred to Tardilly gen. nov., which is similar to Mesodiphthera in the more or less aligned primary forks of R and M placed at about midway between the basal cell and the nodal line, and the backwardly inclined inter-medial cross-vein which runs between M2 and M3. It differs, however, in its smaller size, broader costal space, three-branched M3+4, and differently shaped CuA and CuA2. The new material, all of which is of M. grandis, provides a complete picture of the shape, colour and venation of its tegmen, whereas Tardilly prosboloides (Tillyard) comb. nov., 1922 and Tardilly dunstani (Tillyard) comb. nov., 1922 are still known only from their poorly preserved type specimens. Mesodiphthera and Tardilly exhibit a number of presumed plesiomorphies, viz the costal space much wider than the CuA cell, the basal cell strongly narrowed apically, and the post-nodal cross-vein series closer to the nodal line than the apex, which place it in the probable paraphyletic subfamily Cicadoprosbolinae. A more informed assessment of their relationships, however, must await a comprehensive analysis of the now 29 fossil genera of the family. The Tettigarctidae were the only cicadas of the Mesozoic and the discovery in the Triassic of Australia of Mesodiphthera and Tardilly clearly distinct from the 24 previously known Mesozoic genera, further demonstrates the family’s high degree of structural diversity, and emphasises its almost world-wide distribution in that Era.